An updated perspective on immunoglobulin replacement in chronic lymphocytic leukaemia in the era of targeted therapies - Khan, Sujoy; Allsup, David; Molica, Stefano (Frontiers in Oncology, 2023)
Chronic lymphocytic leukaemia (CLL) is a malignancy of clonally expanded antigen-switched, neoplastic, mature B cells. CLL is characterized by a variable degree of concurrent immunosuppression and secondary hypogammaglobulinemia.B-cell depleting therapies have historically been deployed about a proportion of patients become resistant to multiple lines of treatment with an associated worsening of the degree of immunosuppression and heightened infection risk. Advances in molecular diagnostics and the development of new therapies targeting Brutons tyrosine kinase (Btk) and B-cell lymphoma-2 (Bcl-2)have resulted in novel insights into the cellular mechanisms associated with an increased infection risk and T-cell escape from the complex tumour environment found in CLL. Generally, replacement therapy with polyvalent human immunoglobulin IgG (intravenous or subcutaneous) is indicated in patients with recurrent severe bacterial infections and low immunoglobulin (IgG) levels, but there is no consensus on the threshold IgG level for initiation of such therapy. A proportion of CLL patients have a degree of residual IgG production, with preserved quality of the immunoglobulin molecules, and a definition of ‘IgG quality’ may allow for lower dosing or less frequent treatment with immunoglobulin therapy in these patients. Immunoglobulin therapy has the ability to restore innate immunity and in conjunction with CLL targeted therapies may allow T-cell antigen priming, restore T cell function thereby providing an escape from tumour-associated autoimmunity and the development of an immune-mediated anti-tumour effect. This may translate into the prevention of new emergent malignant B-cell subclones, in addition, facilitate the attainment of deep and long-lasting remissions. This review aims to discuss the mechanisms by which CLL-targeted therapy may exert a synergistic therapeutic effect with immunoglobulin replacement therapy both in terms of reducing tumor bulk and restoration of immune function.